2019
DOI: 10.22139/jobs.492839
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysi̇s for Complai̇nts Related to Chi̇ld - Fri̇endly Hotels

Abstract: Bu sayının ilk çalışmasında Mahmut HIZIROĞLU ve Elif AKKAYA "Küresel Zihniyet ve Ar-Ge Yoğun Kobi'lerin Uluslararasılaşması: Türkiye Biyoteknoloji Sektörü Örneği" başlıklı çalışmalarında Ar-Ge yoğun KOBİ'lerinin uluslararasılaşması üzerine küresel zihniyetin nasıl bir rol oynadığını tartışmaktadırlar. Çalışmada Ar-Ge yoğun KOBİ'lerin küresel zihniyete sahip olup olmadıkları, küresel zihniyete sahip olanların daha çok hangi özellikleri taşıdıkları, hangi unsurların Ar-Ge yoğun Türk KOBİ'lerinde küresel zihniyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Öztürk, Atasoy, and Arıkan (2018) in their studies on hotel businesses, which are considered to be "Child Friendly Hotels" in Antalya, have revealed that hotels do not fully have the feature of being child-friendly. Aslan, Tosun, and Arslan Kurtuluş (2019), on the other hand, investigated the complaints about the hotel businesses that provide ultra all-inclusive concept and are specified as child-friendly hotels and concluded that the complaints about the words "pool, food, bad, clean, money" are in the majority.…”
Section: International Journal Of Economic and Administrative Studiesmentioning
confidence: 99%
“…Öztürk, Atasoy, and Arıkan (2018) in their studies on hotel businesses, which are considered to be "Child Friendly Hotels" in Antalya, have revealed that hotels do not fully have the feature of being child-friendly. Aslan, Tosun, and Arslan Kurtuluş (2019), on the other hand, investigated the complaints about the hotel businesses that provide ultra all-inclusive concept and are specified as child-friendly hotels and concluded that the complaints about the words "pool, food, bad, clean, money" are in the majority.…”
Section: International Journal Of Economic and Administrative Studiesmentioning
confidence: 99%
“…Accommodation businesses that can provide these opportunities are more preferred by families with children and can gain competitive advantage. The factors that have an impact on families with children and that are expected to be in child-friendly hotels are as follows (Emir and Pekyaman, 2010;Aymankuy and Ceylan, 2013;Kim and Park, 2017;Öztürk et al, 2018;Aslan et al, 2019):…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the behaviours of the employees is an important criterion in the tourists' intention to revisit (Aslan et al, 2019) and the families pay attention to the behaviours of the hotel employees towards their children, it is necessary to be careful in the selection of hotel employees in order to increase the rate of preference for child-friendly hotels.…”
Section: Literature Reviewmentioning
confidence: 99%